(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article investigates the scientific and methodological aspects of applying IT outsourcing in the development and sustainable maintenance of enterprise information systems. The study highlights the role of information systems in enterprise activities under digital transformation and examines the importance of IT outsourcing mechanisms in improving management efficiency. The theoretical foundations of IT outsourcing, its organizational and economic model, and the factors influencing enterprise performance are systematically analyzed. Particular attention is given to the interaction between internal IT resources and external service providers in the process of information system development. The research findings show that the rational use of IT outsourcing increases technological flexibility, reduces costs, and improves the quality of information services in enterprises. The conclusions of the article are of scientific and practical significance for enterprise management and the implementation of information technologies.